Sistematización de la experiencia sobre el diseño de un plan de capacitación para los colaboradores de la dirección de talento humano de la Empresa Pública Metropolitana de Movilidad y Obras Públicas (EPMMOP), en el periodo octubre 2016 - agosto 2017 - Paillacho Carlosama, Fernanda Carolina (2018)
The present systematization is executed on a project that was carried out in the Human Talent Management of the Metropolitan Public Company of Mobility and Public Works which has a total of 45 collaborators, this project was executed in the staff training subsystem. The reason by which the project was developed in that subsystem in the first instance was by the dissatisfaction shown by the collaborators, since a high percentage expose that have no knowledge about the existence of a staff training plan in the company, besides to consider that his knowledge does not generate security for functions developing. For this project was used the quantitative methodology that let us to get information when the group is big, the tool that was used in this method is the poll which allowed us to known the collaborators perspectives about the staff training in the company and getting the suggestions to improve that process, the poll was anonymous, in a way that is not interfered by third parties, but the information be provided by the involved people. Also it was used the qualitative methodology which got access to the results of DNC applied by the company, same that allowed us to delimit the topics in which are going to train.